2022
DOI: 10.3390/cancers14153595
|View full text |Cite
|
Sign up to set email alerts
|

Repositioning of Old Drugs for Novel Cancer Therapies: Continuous Therapeutic Perfusion of Aspirin and Oseltamivir Phosphate with Gemcitabine Treatment Disables Tumor Progression, Chemoresistance, and Metastases

Abstract: Metastatic pancreatic cancer has an invariably fatal outcome, with an estimated median progression-free survival of approximately six months employing our best combination chemotherapeutic regimens. Once drug resistance develops, manifested by increased primary tumor size and new and growing metastases, patients often die rapidly from their disease. Emerging evidence indicates that chemotherapy may contribute to the development of drug resistance through the upregulation of epithelial–mesenchymal transition (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 74 publications
0
6
0
Order By: Relevance
“…Considering the inherent chemoresistance, the rapid development of acquired chemoresistance in chemotherapy treatment, and the low effectiveness of cytotoxic treatments in advanced disease stages, innovative and efficient therapies are urgently required. [4,43] A thorough understanding of the genetic origin and tumor microenvironment could help the prognosis, therapy, diagnosis, and prevention of PAAD. Using a number of different methods, such as the accumulation of reactive oxygen species, inhibition of the proteasome, and prevention of angiogenesis, Cu can induce a variety of cell death processes, including apoptosis and autophagy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the inherent chemoresistance, the rapid development of acquired chemoresistance in chemotherapy treatment, and the low effectiveness of cytotoxic treatments in advanced disease stages, innovative and efficient therapies are urgently required. [4,43] A thorough understanding of the genetic origin and tumor microenvironment could help the prognosis, therapy, diagnosis, and prevention of PAAD. Using a number of different methods, such as the accumulation of reactive oxygen species, inhibition of the proteasome, and prevention of angiogenesis, Cu can induce a variety of cell death processes, including apoptosis and autophagy.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the inherent chemoresistance, the rapid development of acquired chemoresistance in chemotherapy treatment, and the low effectiveness of cytotoxic treatments in advanced disease stages, innovative and efficient therapies are urgently required. [ 4 , 43 ] A thorough understanding of the genetic origin and tumor microenvironment could help the prognosis, therapy, diagnosis, and prevention of PAAD.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Qorri et al, [148,149] investigated the therapeutic potential of OP, ASA, and the chemotherapeutic agent gemcitabine (GEM) in pancreatic ductal adenocarcinoma cancer (PDAC) cells. They found that ASA+OP+GEM upended MiaPaCa-2 and PANC-1 pancreatic cell survival mechanisms, including viability, promoting apoptosis, and expressing extra-cellular matrix proteins.…”
Section: Inhibition Of the Neu-1 Complex As A Potential Therapeutic T...mentioning
confidence: 99%
“…In preclinical studies, Qorri et al, [149] reported that a continuous therapeutic targeting of Neu-1 using parenteral perfusion of oseltamivir phosphate (OP) and aspirin (ASA) with gemcitabine (GEM) treatment significantly disrupted tumor progression, critical compensatory signaling mechanisms, EMT program, cancer stem cells (CSC), and metastases in a preclinical mouse model of human pancreatic cancer. In addition, they demonstrated that ASA-and OP-treated xenotumors significantly inhibited the metastatic potential when transferred into animals.…”
Section: Inhibition Of the Neu-1 Complex As A Potential Therapeutic T...mentioning
confidence: 99%
“…This finding may be of significant importance, as it may be the missing link between the anticancer efficacy of NSAIDs and the role of glycosylation in inflammation and sialic acidgenesis [113]. Additionally, the therapeutic targeting of Neu-1 with oseltamivir and aspirin with gemcitabine (GEM) treatment significantly disrupts critical signaling mechanisms, tumor progression, and metastasis in a preclinical mouse model of human pancreatic cancer [114]. The enhanced level of sialic acid was detected in the serum of rosiglitazone-treated diabetic patients and significantly correlated with cardiovascular risk factors.…”
Section: Sialylation and The Efficacy Of Protein Kinase Inhibitors In...mentioning
confidence: 99%